Shooting an Elephant: A study of Hypocrisy; not Heroics - Akter, Shammi (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
Hypocrisy is the practice of engaging in the behavior or activity for which one critics the other. George Orwell’s ‘Shooting an Elephant’ is an essay where hypocrisy is exposed. Because in one side Orwell claims that imperialism is an evil thing and he hates it more bitterly and at the end of the story he establishes himself as an example of a genuine imperialist by performing his noble duty- that really carries his true identity as a hypocrite. It is an act of hypocrisy not heroics in a sense that he shows no courage to express the truth publicly and likes to impose it on the natives. As an agent of British imperialism Orwell shows the tendency of an act of hypocrite by wearing the musk of imperialism and finally unfolded it through the actions and his attitudes. So this paper is a modest attempt to show how hypocrisy is focused through the actions and the descriptions of the narrator who is bold enough in speaking the truth and exposing the lies. Actually the writer as an agent of the British Raj at first knows what he should do to the natives but he tries to show his innocence which becomes an issue here.